Angiographic Studies of Coronary Artery Disease in Rangpur Medical College Hospital (University Heart Journal, 2020)
Background: Coronary artery disease (CAD), one of the leading causes of death is increasing globally. The number of CAD is also increasing in Bangladesh. Rangpur Medical College & Hospital is also providing cardiovascular services to populations from urban, semiurban and rural population of northern region of the country. It started coronary angiography services from June 2011. This paper aims to analyze pattern of coronary artery occlusion in patients undergoing coronary angiography during January to October 2019.Methods: This was a retrospective observational study conducted in the cardiology department. There were a total of 308 cases of diagnostic angiography and coronary interventions done in Rangpur Medical College & Hospital from January to October 2019. Among them 308 cases of coronary angiography done for Acute Coronary Syndrome and Stable Angina, were analyzed using SPSS (Statistical Package for Social Science), version 17.Results: Males were higher in number than females and majority of the patients were at or above 50 years of age. Out of 308 cases 225 had Acute Coronary Syndrome (ACS) and 83 had Stable Angina. 54 out of 308 were found to have normal coronaries. 25 patient with ACS had normal coronary. Out of all the patients with coronary stenosis, 19 had left main disease, 59 had SVD, 62 has DVD, 71 patient had TVD. 9 patients had CTO. 159 patients had severe coronary stenosis. 117 out of 225 ACS patient had more than one coronary artery involved, which is significantly higher than the stable angina group ( p